Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Keterlambatan Laporan Keuangan Perusahaan Yang Terdaftar Di Jakarta Islamic Index Tahun 2019 – 2021 - Efriyadi Efriyadi; Elyanti Rosmanidar; M. Taufik Ridho (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Financial information will have benefits if it is delivered on time to the user, which is closely related to agency theory, where in agency theory it is explained that the owner supervises the agency (employees) so that it can perform more efficiently. The value of timeliness of financial reporting is important for the level of usefulness of the report. This research aims to examine profitability and company size on delays in company financial reports. This research sample consists of 12 companies with 36 financial report data registered with JII for 2019-2021. To test the hypothesis, secondary data was used using the purposive sampling method. The data analysis technique uses multiple linear regression analysis. The results of the analysis show that the profitability variable has a significance value of 0.036, which means that hypothesis X1 has a positive effect on delays in the company's financial reports because the significance value is less than 0.05. The company size variable has a significance value of 0.001, meaning that hypothesis X2 has a significant effect on variable Y because the significance value is less than 0.05